Belanja Pendidikan Tersedot Untuk Gaji Pegawai - IKIP PGRI Semarang, Nurkolis Program Pascasarjana MP (Jurnal Manajemen Pendidikan, 2012)
Abstract: The objectives of this research are to find out real education expenditure: from district budget, direct and indirect expenditure, expenditure of personnel, investment, and operation, and annual student expenditure according to level of education. This research located in Wonosobo and Purworejo districts-Central Java Province in October-December 2011. Findings of this research are: education expenditure including salary is more than 20 % but only less than 10 % if excluded salary, education expenditure allocated higher to indirect than direct expenditure, education expenditure allocated higher to salary than investment and operation, and direct expenditure to state preschool higher than other level of education. Research recommendations are: to manage education budget efficiently and effectively, to do mapping on education personnel, to increase investment and operation expenditure, and finally to allocate education budget proportionally. Abstrak: Penelitian ini bertujuan untuk mengetahui realisasi belanja pendidikan: dari belanja APBD, belanja langsung dan tidak langsung, belanja pegawai, modal, dan barang & jasa, serta belanja langsung persiswa pertahun menurut jenjang pendidikan. Penelitian ini bertempat di Kabupaten Purworejo dan Wonosobo Provinsi Jawa Tengah pada bulan Oktober-Desember 2011. Temuan penelitian ini adalah belanja pendidikan: secara keseluruhan melebihi 20 % dari belanja APBD namun jika tidak termasuk gaji di bawah 10%, lebih banyak untuk belanja tidak langsung, lebih banyak untuk belanja pegawai, belanja langsung persiswa pertahun untuk TKN lebih tinggi dari pada belanja untuk SDN, SMPN, SMAN, atau SMKN. Saran-saran yang diberikan adalah: perlunya pengelolaan anggaran pendidikan secara efisien dan efektif, perlu dilakukan penataan pendidik dan tenaga kependidikan, perlu peningkatan belanja modal dan barang & jasa, serta perlunya penganggaran pendidikan yang proporsional. Key words: education expenditure, direct and indirect expenditure, personnel expenditure, investment expenditure, and operation expenditure. Â